The negative priming paradigm: An update and implications for selective attention - Frings, C; Schneider, K; Fox, E (Springer Verlag, 2015)
Negative Priming (NP) is an influential paradigm in cognitive psychology that was originally developed to measure attentional selection. Yet, up to the mid-1990s, a large number of experimental reports questioned whether the NP effect is based on attentional inhibition and/or episodic retrieval processes. In this review, we summarize findings since the mid-1990s and discuss new and old theoretical approaches to Negative Priming. We conclude that more than one process contributes to NP and that future research should analyze the conditions under which a particular process contributes to NP. Moreover, we argue that the paradigm – although it does not measure a single cognitive process alone – is still a useful tool for understanding selection in cognition. In fact, it might be a virtue of the paradigm that several cognitive processes work here together as selection in nonexperimental contexts is surely a multidimensional process. From this perspective, research on NP is relevant for all research fields analyzing selection. We therefore close our review by discussing the implications of the new evidence on NP for theories of selective attention.